Professional and interpersonal ICT skills in Lebanon. (c2015) - Mallah, Mohamad (2015)
As information technology (IT) development contributes to the economic growth of countries, studying the presence of required skills among IT professionals is critical to the use and diffusion of IT. In fact, enhancing skills in information technology may have a stronger effect in a company than pushing for more ICT investments. Our intent in this study was to determine if there is an IT skill shortage in Lebanon. The research identifies the required and existing skills in the information technology industry in Lebanon since studies on IT skills are lacking in this developing country. Interviews and surveys were conducted with ICT employees and managers. A gap between perceived held skills and perceived required skills was found in the results and different levels of competencies among IT units were also identified.